2022
DOI: 10.2147/dddt.s379794
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Puerarin on Osteogenic Differentiation in vitro and on New Bone Formation in vivo

Abstract: Purpose Puerarin (C 21 H 20 O 10 ) is a phytoestrogen that possesses various pharmacological effect, and several researches have revealed the relationship between puerarin and bone metabolism. This study was aimed to evaluate the potential influence of puerarin on the proliferation and osteogenic differentiation of rat bone marrow-derived mesenchymal stem cells (BMSCs) as well as on new bone formation following rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“… 17 , 26 Other studies have reported that the cartilage range is increased and chondrocytes are more proliferative under expansive forces. 27 , 28 Both endochondral and intramembranous ossifications participate in bone remodeling processes in the MPS. 29 In cases of endochondral ossification, hypertrophic chondrocytes undergo absorption, invasion of new tissues, and mineralization.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 26 Other studies have reported that the cartilage range is increased and chondrocytes are more proliferative under expansive forces. 27 , 28 Both endochondral and intramembranous ossifications participate in bone remodeling processes in the MPS. 29 In cases of endochondral ossification, hypertrophic chondrocytes undergo absorption, invasion of new tissues, and mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…A total of nine male SD rats (specific-pathogen-free) (SPF) (Sibeifu, Beijing, China), weighing 250–300 g, were selected. Preparation of the periodontal defect was as previously described [ 29 , 30 , 31 ]. The alveolar bone defect of about 2 × 1 × 0.8 mm 3 was created in the mesial alveolar bone of the bilateral maxillary first molar mesial root.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 Puerarin (Pue), a candidate drug compound extracted from the plant Pueraria lobata, have strong antioxidant, antiinflammatory and other pharmacological activities. Previous studies have substantiated that Pue can inhibit oxidative stress by inhibiting ATP production and activating AMPK phosphorylation in a streptozotocin-induced mouse model of type I diabetes, 13 regulate NLRP3 inflammatory vesicles through autophagy, which is protective against hyperglycemiainduced chronic vascular disease, 14 mimic an antibacterial peptide, which kills E. coli by binding to lipopolysaccharides and blocking their biological function, 15 and help wound healing by inhibiting NF-κB and MAPK signaling pathways and modulating M2 polarization in macrophages. 16 However, its direct application in wound repair has been limited by low hydrophilicity, poor bioavailability, and low penetration of Pue.…”
Section: Introductionmentioning
confidence: 98%